Courier Legal Relations and Delivery Performance in Shopee Logistics: Hubungan Hukum Kurir dan Kinerja Pengiriman di Shopee Logistics - Bima Dwi Yoga Kresnanda; Sri Budi Purwaningsih (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The rapid growth of e-commerce has increased the importance of logistics services in ensuring efficient product delivery. Specific Background Shopee Express operates as a delivery service that connects sellers and consumers, where courier performance plays a crucial role in achieving delivery targets. Knowledge Gap However, limited studies examine the legal relationship between couriers and warehouse management, particularly regarding delivery performance and transparency in package handover processes. Aims This study aims to analyze the legal relationship between couriers and the Sidoarjo 2 Hub warehouse and its relation to delivery achievement. Results The findings indicate that the legal relationship is governed through a vendor partnership agreement that regulates rights and obligations, where courier discipline affects delivery speed and accuracy, while lack of transparency in package handover may lead to operational risks. Novelty This study highlights the role of transparency in package distribution alongside contractual legal relationships in logistics operations. Implications The results suggest the need for improved operational procedures and clearer legal arrangements to ensure accountability and reduce delivery-related disputes. Keywords: Courier, Legal Relationship, Delivery Performance, E-commerce Logistics, Partnership Agreement Key Findings Highlights Contractual arrangements define operational responsibilities Work discipline shapes service consistency in distribution Package handling procedures reveal operational vulnerabilities